5-3(x-1)=2x-(x+4)

Simple and best practice solution for 5-3(x-1)=2x-(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(x-1)=2x-(x+4) equation:


Simplifying
5 + -3(x + -1) = 2x + -1(x + 4)

Reorder the terms:
5 + -3(-1 + x) = 2x + -1(x + 4)
5 + (-1 * -3 + x * -3) = 2x + -1(x + 4)
5 + (3 + -3x) = 2x + -1(x + 4)

Combine like terms: 5 + 3 = 8
8 + -3x = 2x + -1(x + 4)

Reorder the terms:
8 + -3x = 2x + -1(4 + x)
8 + -3x = 2x + (4 * -1 + x * -1)
8 + -3x = 2x + (-4 + -1x)

Reorder the terms:
8 + -3x = -4 + 2x + -1x

Combine like terms: 2x + -1x = 1x
8 + -3x = -4 + 1x

Solving
8 + -3x = -4 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
8 + -3x + -1x = -4 + 1x + -1x

Combine like terms: -3x + -1x = -4x
8 + -4x = -4 + 1x + -1x

Combine like terms: 1x + -1x = 0
8 + -4x = -4 + 0
8 + -4x = -4

Add '-8' to each side of the equation.
8 + -8 + -4x = -4 + -8

Combine like terms: 8 + -8 = 0
0 + -4x = -4 + -8
-4x = -4 + -8

Combine like terms: -4 + -8 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 3x-5+5x=52 | | .5x+2=0 | | x-16+16=79+16 | | 1-3x+5x=17 | | 6x-2=4+3x-2 | | (2n)(4n+2)= | | X+2(3.5)=7 | | 1+5x-3x=-17 | | .5x+2=1 | | 0.3n=0.2 | | 9+6x-3x=36 | | 2x+2=96 | | 13=1-2x-2x | | 4x-3-2x=-3 | | 26=3c-3(6-2c) | | Vf=vi+(9.81)6 | | 4x-5=-19 | | 7x+1-2x=41 | | 2x^2-4x+6y-10=0 | | -27+6d=7(4d+8) | | 8+4x-3x=-2 | | 13x-31+8x-176=180 | | rt-2n=fort | | 3x-4(x+3)=22 | | 2(y+5)=y+13 | | 23=4x-x-10 | | (10x^2)+3=11x | | -3(n-6)=12(n-4)+7n | | 12y-15y=584 | | 8(t-4)+7t=5(3t+4)-8 | | -3x-3-x=21 | | 3x-3+4x+8=75 |

Equations solver categories